2000
DOI: 10.1080/08927020008022373
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear QSAR Treatment of Genotoxicity

Abstract: The nonlinear QSAR approach using the Chebyshev polynomial expansion and neural networks has been applied for the prediction of genotoxicity of compounds. The mutagenic toxicity of heteroaromatic and aromatic amines, measured by the Ames test, was correlated with the molecular descriptors calculated from the molecular structures using quantum-chemical methods. The quantitative models obtained were compared with the results of the linear QSAR treatment. The descriptors appearing in the models reveal the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
(7 reference statements)
1
9
0
Order By: Relevance
“…It is only possible to use linear regression methods if the activity descriptor relation is linear. However the relationship between biological activity and the molecular descriptors are not always linear [262]. Machine learning approaches such as neural networks and support vector machine methods are used to generate QSAR models to address this issue of non-linear fitting [263265].…”
Section: Reviewmentioning
confidence: 99%
“…It is only possible to use linear regression methods if the activity descriptor relation is linear. However the relationship between biological activity and the molecular descriptors are not always linear [262]. Machine learning approaches such as neural networks and support vector machine methods are used to generate QSAR models to address this issue of non-linear fitting [263265].…”
Section: Reviewmentioning
confidence: 99%
“…However, we were able to show that other simpler structure-based descriptors can be an efficient replacement for logP. A combination of step forward selection of descriptors and back-propagation NN improved the quality of the model with slightly different descriptor content of the model, indicating the possible non-linear relationship between structural determinants and genotoxicity of the compounds [131].…”
Section: Qsar On Toxicitymentioning
confidence: 91%
“…In recent years, the literature concerning ANN as applied to QSPR/QSAR has grown drastically, suggesting that the importance of applications of ANN in molecular modeling is a major driving force. Among numerous studies using ANN in QSPR/QSAR, major contributions are due to the groups of Jurs, Zupan and Gasteiger, and Zefirov and ourselves among others. These authors have shown that the ANN models frequently possess better predictive characteristics compared to models using standard multilinear regressions.…”
Section: Introductionmentioning
confidence: 99%